Bollywood Lyrics: Stereotypical Miss-Representation - Khan, Shehreen Ataur (EAST WEST JOURNAL OF HUMANITIES, 2017)
This paper examines some of the popular songs of the Indian Film Industry where the roles of men and women are fixed stereotypically. Some of these lyrics are written by legendary Indian lyricists such as Gulzar (Sampooran Singh Kalra), Jatin-Lalit and so on. Despite of having clear evidences of gender biased language, almost all of these songs became exceedingly popular throughout the decades and the legacy of using such stereotyped lyrics is going on in the present times as well. The paper goes through some of those lyrics and explores the representations of men and women in them. If analyzed carefully, one would realize that in more or less every song, women are portrayed doing household chores, getting dolled up and waiting for their men, while men are mostly represented as women’s saviors and voyeurs. With references to the cultural theorists such as Morag Shiach and Naomi Wolf, this paper deals with the complex question of gender representations in Bollywood songs and shows how such lyrics have the capacity to influence the listeners as well as having an impact on their ideas eventually. While searching for the reasons behind these redundant stereotypes, the paper also delves into feminist theorists like Gilbert and Gubar to show the impact of the imbalance in male-femalelyricists ratio in the industry. The purpose of this paper is thus twofold; firstly it exhibits that Bollywood industry has still been using the same stereotypical framework throughout the last 100 years and secondly itanalyzes the gender insensitive traits that are working as a perpetuating tool of patriarchy.